Prenatal exposure to perfluoroalkyl substances and thyroid hormone concentrations in cord plasma in a Chinese birth cohort - Liang, Hong (Environ Health, 2020)
BACKGROUND: Evidence of associations between prenatal exposure to perfluoroalkyl substances (PFASs) and fetal thyroid hormones (THs) is controversial, and few studies have estimated the associations, while addressing the high correlations among multiple PFASs. We aimed to examine the associations between prenatal PFAS exposure and thyroid hormone concentrations in cord blood. METHODS: A total of 300 mother-infant pairs from the Shanghai-Minhang Birth Cohort Study were included. We measured the concentrations of eight PFASs in maternal plasma samples collected at 12–16 gestational weeks, as well as those of total thyroxine (T4), free T4 (FT4), total triiodothyronine (T3), free T3 (FT3), and thyroid stimulating hormone (TSH) in cord plasma. We estimated the associations between maternal PFAS concentrations and TH concentrations using linear regression and Bayesian kernel machine regression (BKMR) models. RESULTS: In BKMR models, higher PFAS mixture concentrations were associated with increased T3 concentrations, and there were suggestive associations with increased FT3 concentrations. For single-exposure effects in BKMR models, a change in PFDA, PFUdA, and PFOA concentrations from the 25th to 75th percentile was associated with a 0.04 (95%CrI: − 0.01, 0.09), 0.02 (95%CrI: − 0.03, 0.07), and 0.03 (95%CrI: − 0.001, 0.06) nmol/L increase in T3 concentrations, respectively. PFOA, PFNA, and PFDA were the predominant compounds in PFASs-FT3 associations, and the corresponding estimates were 0.11 (95% CrI: 0.02, 0.19), − 0.17 (95% CrI: − 0.28, − 0.07), and 0.12 (95% CrI: − 0.004, 0.24) pmol/L, respectively. A change in PFNA and PFOA concentrations from the 25th to 75th percentile was associated with a − 1.69 (95% CrI: − 2.98, − 0.41) μIU/mL decrease and a 1.51 (95% CrI: 0.48, 2.55) μIU/mL increase in TSH concentrations. The associations of PFOA and PFNA with T3/FT3 were more pronounced in boys, while those with TSH were more pronounced in girls. CONCLUSION: Our results suggest that prenatal exposure to multiple PFASs was associated with thyroid hormones in cord blood. However, individual PFAS had varied effects—differing in magnitude and direction—on fetal thyroid hormones. SUPPLEMENTARY INFORMATION: Supplementary information accompanies this paper at 10.1186/s12940-020-00679-7.